Fortification of dairy-free yoghurt with bioactive protein from solid-state fermented brewers’ spent grain - Jiao Zhang; Ariane Perez-Gavilan; Adriana Cunha Neves (Applied Food Research)
High-protein food products were gaining popularity due to growing health awareness. Brewers’ spent grain (BSG), a brewing by-product, has been recognised as a potential source of bioactive protein for functional food development. In this study, protein from solid-state fermented BSG (FBSGP) demonstrated significant antioxidant and anti-hypertensive potential and remained stable post-simulated gastrointestinal digestion (SGID). As a result, it was chosen as a functional ingredient in yoghurt formulations at 0, 1, 2.5, and 5% ratios. Furthermore, the colour profiles, physicochemical properties, and sensory attributes of the protein-added yoghurts were investigated. Overall, protein incorporation increased the yoghurt's pH and decreased syneresis, with no significant impact on viscosity. A focus group of 12 panellists was formed to undertake the sensory assessment. Price, flavour, and protein content were ranked as the most important attributes by the panellists when buying yoghurts. Furthermore, yoghurts containing 2.5 and 5% protein were further assessed by 12 panellists in terms of their sensory characteristics in comparison to the control yoghurt. 2.5% protein-added yoghurt had higher or similar averages of colour, texture, taste, and mouthfeel, as well as an overall preference for the yoghurt control, whereas the yoghurt containing 5% protein exhibited lower overall acceptance. The preference for the 5% protein-fortified yoghurt remained similar before and after informing the panellists of the incorporation of protein. Additionally, a positive willingness with a 20–50% price premium for protein-added yoghurt with health benefits was observed. In conclusion, fermented BSGP has the potential to be an alternative vegan protein ingredient for the production of functional yoghurt.